A New Method for Identifying Cochlear Ossification in Cochlear Implant Candidates with Deafness following Meningitis. (23rd August 2013) - Ichikawa, Kazunori; Kashio, Akinori; Ochi, Atushi; Karino, Shotaro; Sakamoto, Takashi; Kakigi, Akinobu; Yamasoba, Tatsuya
Abstract : Objectives: To develop a new method to determine the presence of intracochlear ossification and/or fibrosis in candidates for cochlear implantation (CI) with deafness following meningitis. Methods: This study involved 13 patients (15 ears: normal structures, soft tissue alone, partial bony occlusion, and complete bony occlusion in 4, 3, 2, and 6 ears, respectively) with profound deafness due to meningitis who underwent CI. We measured the radiodensity in Hounsfield Units (HU) using 0.5‐mm‐thick, axial, high‐resolution computed tomography (CT) image slices at 3 different points in the basal turn, including the fenestration site and inferior and ascending segment sites, which were located along the electrode‐insertion path. Pixel‐level analysis on the DICOM viewer yielded actual CT values of intracochlear soft tissues by eliminating the partial volume effect. The values were compared with the intraoperative findings. Results: Values for ossification (n = 12) ranged from +547 HU to +1137 HU (n = 12); for fibrosis (n = 11), from +154 HU to +574 HU (n = 11); and for presence of fluid (n = 22), from −49 HU to +255 HU. From these values, we developed 2 presets of window width (WW) and window level (WL): 1) WW: 1800, WL: 1100 (200 HU to 2000 HU) and 2) WW: 1500, WL: 1250 (500 HU to 2000 HU). The results using these 2 presets corresponded well with the intraoperative findings. Conclusions: Our new method is easy and feasible to preoperatively determine the presence of cochlear ossification and/or fibrosis that develop following meningitis.